2006
DOI: 10.1111/j.1460-9568.2006.05207.x
|View full text |Cite
|
Sign up to set email alerts
|

Mouse galectin‐1 inhibits the toxicity of glutamate by modifying NR1 NMDA receptor expression

Abstract: One of the major causes of neuronal death in neurodegenerative disease is excitotoxicity from the neurotransmitter glutamate. This form of cell death could arise from either excess levels of glutamate due to decreased astrocyte clearance or due to increased susceptibility. We have identified galectin-1, a galactose-binding lectin, as a potential neuroprotective factor secreted by astrocytes. Our results show that both native and recombinant galectin-1 protects mouse and rat cerebellar neurons from the toxic ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 39 publications
(51 reference statements)
1
24
0
Order By: Relevance
“…Studies have showed that secreted endogenous Gal-1 can act on the relevant receptors and induce downstream effects [8]. We here showed that endogenous Gal-1 can be induced by anoxia, and exogenous Gal-1 contributed to the astrocytic BDNF production.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…Studies have showed that secreted endogenous Gal-1 can act on the relevant receptors and induce downstream effects [8]. We here showed that endogenous Gal-1 can be induced by anoxia, and exogenous Gal-1 contributed to the astrocytic BDNF production.…”
Section: Discussionsupporting
confidence: 55%
“…We would like to elucidate that recovery of ischemic rats might come from multiple effects of several pathways because Gal-1 takes a general role in CNS [8,10,38]. Although dependable data about the dose of astrocytic BDNF valuable for neuroprotection has not been identified, the increased production of astrocytic BDNF may partly mediate this neuroprotective effect at least.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enzymatic and mechanical treatments for the dissociation of DRG cells, together with disruption of interactions between neurons and non-neuronal cells are detrimental to neurons. Therefore, GAL-1 expressed in cultured neurons may function as a stress marker protein (Iwamoto et al, 2010) and/or a cytoprotective molecule (Lekishvili et al, 2006) during in vivo-in vitro replacement. Western blot analysis.…”
Section: Gdnf Upregulates Protein Expression Of Gal-1 In Cultured Drgmentioning
confidence: 99%